INDONESIAN NAVY OFFICERS PLACEMENT USING ANALYTIC NETWORK PROCESS (ANP) (CASE STUDY: PATROL SHIPS COMMANDER) - Oyu Mulia Sukmana; Adithya Sudiarno; Joko Purnomo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Indonesian Navy (TNI AL) as one of the core components of the national defense system, carries out the task of the marine dimension in the defense sector and protects the law and maintains security in the sea area in accordance with the provisions of national law and ratified international law. The readiness of the Navy's organization is supremely determined by the components of the Navy's strength, which consists of personnel and the main equipment of the weapon system (defense equipment). The placement of positions, especially for the position of commander of a patrol ship, is a process to obtain the best human resources. This study focuses on analyzing and determining the criteria for the position of the KRI Commander on the Patrol Ship (as one of the important positions in the Indonesian Navy). The Analytic Network Process Model can be used as an instrument in determining alternative officers fulfill the requirements for occupying positions. Hasil Kuisioner akan digunakan sebagai input dalam software Superdecision. Hasil dari software tersebut adalah bobot dari masing-masing subCriteria yang dapat digunakan dalam penilaian seleksi Komandan Kapal Patroli serta dapat diketahui peringkat dari alternatif calon pada model. The results of data processing using Super Decisions software can be known as alternative priorities by looking at the weight value of each alternative, namely Priority 1 is Candidate A with a weight value of 0.384181, Priority 2 is Candidate B with a weight value of 0.309020 and Priority 3 is Candidate C with a weight value of 0.306799. Keywords: ANP, Personel Placement, Patrol Ship